1995
DOI: 10.1016/0895-7061(94)00178-e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging compared to echocardiography to assess left ventricular mass in the hypertensive patient

Abstract: Echocardiography (ECHO) is useful to document changes in left ventricular mass (LVM) in groups of patients, but may be too variable for use in the individual patient. Magnetic resonance imaging (MRI) may be a more precise and reliable method to quantify the mass of the left ventricule. This study reports the accuracy, precision, and reliability of LVM estimates by MRI as compared to data obtained by ECHO in hypertensive patients. Accuracy referred to the comparison of LVM by MRI to anatomical LVM determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
209
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(220 citation statements)
references
References 34 publications
6
209
1
4
Order By: Relevance
“…Demonstration of LVM regression using echocardiographic methods also requires relatively large cohorts of patients because of the high observer and interstudy variability. 18,[22][23][24] Cardiac MRI has become the technique of choice for precise measurements of LVM. This 3D technique, with excellent definition of endocardial and epicardial borders, is highly reproducible, which means that a much smaller sample size is needed to detect LVM regression in clinical trials.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstration of LVM regression using echocardiographic methods also requires relatively large cohorts of patients because of the high observer and interstudy variability. 18,[22][23][24] Cardiac MRI has become the technique of choice for precise measurements of LVM. This 3D technique, with excellent definition of endocardial and epicardial borders, is highly reproducible, which means that a much smaller sample size is needed to detect LVM regression in clinical trials.…”
Section: Perspectivesmentioning
confidence: 99%
“…LVM, as measured by cardiac MRI, has been validated in animal studies 20,21 and has been demonstrated to be more accurate and reproducible than M-mode and 2D echocardiography measurements. 18,22,23 As a result of the superior accuracy and reproducibility, fewer subjects are needed in research studies using cardiac MRI. 24 The aim of our study was to evaluate the Sokolow-Lyon voltage, Cornell sex-specific voltage, Sokolow-Lyon product, and Cornell product criteria against LVM index as measured by cardiac MRI in a large cohort of patients.…”
mentioning
confidence: 99%
“…Although MRI appears to be more precise and reliable for measuring LVM, 45 it is limited by cost, fixed facilities and claustrophobia. The echocardiography widely used permits the realisation of largescale studies which can then include a representative population of hypertensive LVH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging was used as the gold standard, as it has been extensively validated against autopsy in the 3-Dimensional (3-D) measurement of LVM. 8,9 Clinical Investigations continued…”
Section: Introductionmentioning
confidence: 99%